The Influence of Price Perception And Trust on Online Shopping Purchase Intention in Tokopedia E-Commerce - Ibadi, Mohammad Syarif; Supriyono, Supriyono (International Journal of Economics (IJEC), 2025)
This study aims to determine the effect of Price Perception and Trust variables on Purchasing Interest for Tokopedia E-Commerce Shopping partially.This type of research is quantitative. The population in this study were Shopee consumers in Surabaya, aged 17 years who had made at least two purchases at Shopee e-commerce. The sample of this research is 78 respondents. The sampling technique used in this study was no change sample. Collecting data using a questionnaire as a source of primary research data. While the data processing technique used is Partial Least Square (PLS). Based on the results of the study it can be concluded that Price Perception has a positive effect on Purchasing Interest, Trust has no effect on Purchasing Interest.